2019
DOI: 10.1093/ntr/ntz173
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Why Farmers Grow Tobacco: Evidence From Malawi, Kenya, and Zambia

Abstract: Introduction Tobacco production continues to increase in low- and middle-income countries creating complications for tobacco control efforts. There is the need to understand and address the global tobacco leaf supply as a means of decreasing tobacco consumption and improving farmers livelihoods in line with Article 17 of the WHO Framework Convention on Tobacco Control. This study aims to understand the reasons why farmers grow tobacco and identify factors that influence these reasons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…What we see are decisions that are primarily based on the structured supply chain and corresponding benefits of contractual relationships with leaf-buying companies, such as provision of inputs and access to loans. This is becoming a ubiquitous theme in studies that have examined why farmers choose to grow tobacco irrespective of the geographic location [6,17,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…What we see are decisions that are primarily based on the structured supply chain and corresponding benefits of contractual relationships with leaf-buying companies, such as provision of inputs and access to loans. This is becoming a ubiquitous theme in studies that have examined why farmers choose to grow tobacco irrespective of the geographic location [6,17,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Selection of participants for the focus groups was done during data collection of a parallel tobacco farmer survey in each of the regions. Enumerators, the individuals administering the survey to tobacco farmers, which is another component of our research project [6,14,18], identified 10-15 of the most experienced tobacco farmers in each county who were willing to provide additional information during the FGD. Efforts were made to generate some variation by gender, age, and the extent to which farmers had diversified livelihoods.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations